Literate practices in confirmation catechesis in a Catholic church - Almeida Goshi, Claudia Kazuko (2011)
This paper uses an ethnographic approach to describe and explain the language used by a confirmation group of a Catholic Church concerning a specific text: the Bible. Therefore, unlike the "great divide" proposal developed by Jack Goody, Erick Havelock and Walter Ong, where a clear dichotomy is raised among literacy and social context; in this paper the use of New Literacy Studies methodological tools has been taken into account in order to frame oral and written language uses in specific social contexts in which they acquire meaning through the values that underlie the literacy practices of individuals.